Association of ambulatory arterial stiffness index with sEPCR in newly diagnosed hypertensive patients. (21st October 2015) - Yilmaz, Hakki; Cakmak, Muzaffer; Inan, Osman; Darcin, Tahir; Aktas, Aynur; Gurel, Ozgul Malcok; Bilgic, Mukadder Ayse; Bavbek, Nuket; Akcay, Ali
Abstract: Aim : Increased arterial stiffness is strongly associated with cardiovascular diseases, while thrombotic events are more common than hemorrhagic events in hypertensive patients. Markers of a hypercoagulable state may also predict future cardiovascular events in hypertensive patients. Here, we speculated that increased arterial stiffness might lead to the development of a hypercoagulable state that can play a role in the thrombotic complications of hypertension. Soluble endothelial protein C receptor (sEPCR) is one such marker of hypercoagulation. The ambulatory arterial stiffness index (AASI) could be accepted as a non-invasive measure of arterial stiffness. The aim of this study was to investigate association of AASI with levels of sEPCR in newly diagnosed hypertensive patients. Materials and methods : The study included 263 newly diagnosed essential hypertensive patients and 55 healthy normotensive controls. All subjects underwent 24 h ambulatory blood pressure monitoring (ABPM); the AASI was derived from ABPM tracings. Plasma sEPCR was measured by ELISA. Results : Hypertensive patients ( n  = 263) had higher AASI, C-reactive protein (CRP) and sEPCR versus the normotensive healthy group ( n  = 55). Univariate analysis showed that AASI was positively associated with age ( r  = 0.212, p  <  0.001) body mass index ( r  = 0.412, p  < 0.001), pulse pressure ( r  = 0.350, p  < 0.001), plasma sEPCR ( r  = 0.894, p  < 0.001), 24-h heart rate ( r  = 0.176, p  = 0.001) and inversely related to high-density lipoprotein (HDL) ( r  =  − 0.293, p  < 0.001). Multivariate analyses revealed that sEPCR and HDL are independently correlated to AASI. Conclusion : We suggest that increased AASI is associated with elevated sEPCR. It might be responsible for subsequent thrombotic events in newly diagnosed hypertensive patients.